275 MST1 MEDIATES DOXORUBICIN-INDUCED CARDIOMYOPATHY BY SIRT3 DOWNREGULATION. (15th December 2022) - Schirone, Leonardo; Vecchio, Daniele; Forte, Maurizio; Sciarretta, Sebastiano
Abstract: Introduction: Heart failure is a major side effect of doxorubicin (DOX) treatment in patients with cancer. However, the mechanisms underlying the development of DOX-induced cardiomyopathy (DCM) need to be addressed. Here, we demonstrate that the serine/threonine kinase MST1, a major Hippo pathway component, contributes to the development of DOX-induced myocardial injury. Hypothesis: The inhibition of MST1 protects from DCM by preserving SIRT3 expression Methods: C57BL/6J WT mice and mice with cardiomyocyte-specific dominant-negative MST1 (kinase-dead) overexpression received 3 weekly injections of DOX, reaching a final cumulative dose of 18 mg/kg. Echocardiographic, histological and biochemical analyses were performed 6 weeks after the first administration of DOX. Results: MST1 signaling was significantly activated in cardiomyocytes in response to DOX treatment in vitro and in vivo. Wild-type (WT) mice treated with DOX had reduced fractional shortening (46, 1±1, 77 vs. 31, 1±1, 07, n=7-11) and mitochondrial abnormalities (3, 7±0, 93 vs. 10, 2±1, 5, n=12 microscopic fields from 3 independent samples). However, systolic dysfunction was abolished in mice with cardiomyocyte-specific overexpression of dominant-negative MST1 (DN-MST1) (31, 1±1, 07 vs. 46, 3±1, 13, n=11) or treated with the MST1 inhibitor 'XMU-MP-1' (37, 5±1, 8 vs. 46, 6±1, 87, n=8), indicating that MST1 inhibition attenuates DOX-induced cardiac dysfunction. Also, DOX treatment led to a significant downregulation of cardiac levels of SIRT3 (1±0, 12 vs. 0, 6±0, 11, n=4), a deacetylase involved in mitochondrial protection, in WT mice, which was rescued by MST1 inhibition (0, 6±0, 11 vs. 1, 3±0, 04, n=4). Pharmacological inhibition of SIRT3 blunted the protective effects of MST1 inhibition (44, 5±1, 55 vs. 32, 5±2, 33, n=4), indicating that SIRT3 downregulation mediates the cytotoxic effects of MST1 activation in response to DOX treatment. Finally, we found a significant upregulation of MST1 levels in human myocardial tissue of cancer patients treated with DOX (1, 5±0, 23 vs. 2, 4±0, 12, N=81-123 cells from 3 different patients). Conclusion: MST1 contributes to DOX-induced cardiomyopathy by promoting mitochondrial damage through SIRT3 downregulation in cardiomyocytes.